Intestinal Innate Antiviral Immunity and Immunobiotics: Beneficial Effects against Rotavirus Infection - Villena, Julio; Vizoso-Pinto, Maria Guadalupe; Kitazawa, Haruki (Frontiers in Immunology, 2016)
The mucosal tissues of the gastrointestinal tract are the main portal entry of pathogens such as rotavirus (RVs), which is a leading cause of death due to diarrhea among young children across the globe and a major cause of severe acute intestinal infection in livestock animals. The interactions between intestinal epithelial cells (IECs) and immune cells with RVs have been studied for several years, and now it is known that the innate immune responses triggered by this virus can have both beneficial and detrimental effects for the host. It was demonstrated that natural RVs infection in infants and experimental challenges in mice result in the intestinal activation of pattern recognition receptors (PRRs) like Toll-like receptor 3 (TLR3) and striking secretion of pro-inflammatory mediators that can lead to increased local tissue damage and immunopathology. Therefore, modulating desregulated intestinal immune responses triggered by PRRs activation are a significant promise for reducing the burden of RVs diseases. The ability of immunoregulatory probiotic microorganisms (immunobiotics) to protect against intestinal infections such as those caused by RVs, are among the oldest effects studied for these important group of beneficial microbes. In this review, we provide an update of the current status on the modulation of intestinal antiviral innate immunity by immunobiotics, and their beneficial impact on RVs infection. In addition, we describe the research of our group that demonstrated the capacity of immunobiotic strains to beneficially modulated TLR3-triggered immune response in IECs, reduce the disruption of intestinal homeostasis caused by intraepithelial lymphocytes, and improve the resistance to RVs infections.